Affection and Abuse: Technology Use in Adolescent Romantic Relationships. Issue 1 (1st January 2019) - Mosley, Marissa A.; Lancaster, Morgan
Abstract: Communication technologies benefit romantic relationships in terms of connection, but can also bring potential harm. Positive relational outcomes of adolescent technology use (i.e., increased emotional connection) have been examined separately from negative outcomes (i.e., unwanted monitoring of whereabouts) in previous research. However, the current study utilized hierarchical multiple regression to explore whether variance in both positive and negative relational outcomes could be explained by time spent online. Results suggest that time spent online predicts both positive relationship quality and cyber dating abuse after controlling age and gender. Implications include a greater understanding of the intersection between technology and adolescent relationships.